Enhancement of dieckol extraction yield from Ecklonia cava through optimization of major variables in generally recognized as safe solvent-based process - Shin, Hyeonmi; Lee, Jeongho; Bae, Jihyun; Lee, Kang Hyun; Yoo, Hah Young; Park, Chulhwan (Frontiers in Marine Science, 2023)
Ecklonia cava (EC), an edible brown macroalga abundant in intertidal areas of East Asia (Korea, Japan, and China), contains high-value bioactive compounds such as dieckol, which has antifungal, anti-inflammatory, antitumor, and antihyperlipidemic activities. However, no studies have been reported on the utilization of EC as a biorefinery feedstock, and the design of a more economical and high-yield process is required for the utilization of dieckol for the human healthcare industry. In this study, we designed a bioprocess for the high-yield recovery of dieckol from EC in a generally recognized as safe (GRAS) solvent to facilitate its application in the food and healthcare industries. Preliminary studies identified ethanol as an efficient solvent with the highest dieckol extraction yield (2.9 mg/g biomass). In order to maximize the recovery of dieckol from EC, the major extraction variables (solvent concentration, reaction temperature, and reaction time) were optimized based on statistical methods. Based on the predictive model, the numerical optimization determined that the solution with the highest dieckol content per weight of extract (62.6 vol% ethanol concentration, 54.2°C temperature, 13.2 min) was the optimal extraction condition. Under the determined conditions, the dieckol yield from EC achieved 6.4 mg dieckol/g EC (95.5% agreement with the predicted value). The designed process offers several advantages, including improving the utilization feasibility of EC, utilizing GRAS solvents with potential human applications, short extraction time (13.2 min), maximized process yield, and the highest dieckol recovery compared to previous reports.